2011
DOI: 10.1590/s1516-05722011000500013
|View full text |Cite
|
Sign up to set email alerts
|

Características produtivas do manjericão (Ocimum basilicum L.) em função do espaçamento entre plantas e entre linhas

Abstract: .br 1 . RESUMO:O presente trabalho teve como objetivo avaliar o efeito de diferentes densidades de plantas nas características produtivas do manjericão (Ocimum basilicum L.), cultivado a campo. O experimento foi conduzido na estação experimental pertencente à UNIOESTE, em Marechal Cândido Rondon -PR, no período de setembro a dezembro de 2010. O delineamento utilizado foi o de blocos casualizados, em esquema fatorial 5x2, com três repetições. O primeiro fator foi constituído de cinco espaçamentos entre plantas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 5 publications
(1 reference statement)
0
5
1
11
Order By: Relevance
“…The results of the number of leaves of this experiment for the cultivar Tuscan, provided 53% less leaves than in the study conducted by Favorito et al (2011) for the same cultivar. Luz et al (2014) also found plant height results higher than that observed in this study.…”
Section: Resultscontrasting
confidence: 47%
“…The results of the number of leaves of this experiment for the cultivar Tuscan, provided 53% less leaves than in the study conducted by Favorito et al (2011) for the same cultivar. Luz et al (2014) also found plant height results higher than that observed in this study.…”
Section: Resultscontrasting
confidence: 47%
“…According to the literature, this crop adapts well to subtropical and temperate climates, warm and wet weather; and can be grown throughout the year. The plant tolerates low temperatures, but its development is slower in such conditions (Favorito et al, 2011).…”
Section: Soil Analysis Resultsmentioning
confidence: 99%
“…A maior área foliar no espaçamento 1,0 x 1,0 m pode ser devida à maior exposição das folhas à luz difusa, resultando no aumento da área foliar específica, pela maior expansão foliar e maior acúmulo de fotoassimilados, o que contribui para maior produção de biomassa (Favorito et al, 2011).…”
Section: Resultsunclassified